Hubungan Jenis Persalinan dan Dukungan Tenaga Kesehatan dengan Keberhasilan ASI Eksklusif - Rusdiarti, Rusdiarti (ARTERI : Jurnal Ilmu Kesehatan, 2023)
The Ministry of Health of the Republic of Indonesia has set a target to increase exclusive breastfeeding up to 80%. However, this policy has not yet obtained optimal results. Based on data from the Indonesian Health Profile, the coverage of babies who receive exclusive breastfeeding in 2020 is only 66.1%. This is due to several obstacles in exclusive breastfeeding, namely: lack of socialization of the lack of exclusive breastfeeding and the support of health workers, especially midwives, is still considered lacking. This type of research is descriptive quantitative using a cross sectional approach. The population of this study were postpartum mothers in Jember Regency. The number of samples studied was 30 respondents using a purposive sampling technique that met the inclusive criteria, namely: postpartum mothers 1 to 6 weeks, and able to operate android mobile phones. For the exclusion criteria, namely; Postpartum mothers who experience breast problems/abnormalities; and mothers who live in difficult signal areas. The data obtained were analyzed using SPSS statistics and Fisher's Exact Test with an alpha value of 5%. The results obtained for the type of delivery were that there was no significant relationship between the type of delivery and the success of exclusive breastfeeding mothers with a value of p = 0.140 (OR = 3.5; 95% CI 0.43-28.13). While the results for the support of health workers who carried out the Fisher's exact test showed that there was a significant relationship between the support of health workers and the success of mothers in exclusive breastfeeding with a value of p = 0.007 (OR = 0.83; 95% CI 0.12 - 5.5). Based on the results of the study it can be concluded that the need for understanding for mothers regardless of the type of delivery does not affect the success of breastfeeding and the need for support from health workers, especially midwives in helping mothers to successfully breastfeed their babies.